Macroeconomic determinants of Peruvian migration flows - Barahona U., Planck (2020)
The objective of this paper is to determine the variables associated with the weight that Peruvian immigration has in the total immigration in Chile for the period 2005-2014. The initial hypothesis is that the Peruvian migratory flow has a social and economic component. The results showed that an increase in the Human Development Index (HDI) in favor of Chile increases the migratory flow. On the other hand, a larger education budget in favor of Chile decreases the migratory flow of Peruvian citizens.